The Internalization of Religious Moderation Values Through Islamic Religious Education in Junior High School - Afdhillah Amin, Adetya Maulana; Matsum, Hasan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine how education planning, education implementation, and the obstacle to applying religious moderation values through Islamic religious education (PAI) at Maitreyawira Asahan Private Junior High School. This qualitative study uses a case study approach held at Maitreyawira Asahan Private Junior High School. The research data takes the shape of religious moderation values in schools. Data were gathered from teachers, students, and other stakeholders at Maitreyawira Asahan Private Junior High School. Data collection methods include observation, interviews, and documentation. At the same time, data analysis uses data reduction, data display, generating conclusions, and verification. The findings of this study demonstrated that internalization of religious moderation values could be accomplished through learning Islamic religious education, and teachers are expected to be able to provide religious guidance to students by carrying out educational planning activities and implementing education through learning Islamic religious education in order to instill tolerance in students.